2023
DOI: 10.1111/1467-9817.12426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring moderational and mediational relations among word reading, vocabulary, sentence processing and comprehension for struggling adult readers

Abstract: Background: A significant portion of adults struggle to read at a basic level. Word reading (defined here as decoding and word recognition) appears to play a pivotal role for this population of readers; however, less is known about how word reading relates to other important semantic processes (e.g., vocabulary, sentence processing) known to account for a large portion of variance in reading comprehension. This study used the Reading Systems Framework to explore the extent that moderational and mediational rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
(177 reference statements)
1
1
0
Order By: Relevance
“…Likewise, vocabulary played an important role in the WAIS Vocabulary test, by defining the concepts in terms of oral vocabulary. These results are in line with those obtained by Feller et al [90], who concluded that vocabulary significantly mediates the relationship between word reading and comprehension. Similarly, a study by Tran et al [91] found similar results in a test of vocabulary breadth and depth in a sample of 103 adults with low literacy skills.…”
Section: The Role Of Vocabulary As a Mediating Variable In Reading Co...supporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, vocabulary played an important role in the WAIS Vocabulary test, by defining the concepts in terms of oral vocabulary. These results are in line with those obtained by Feller et al [90], who concluded that vocabulary significantly mediates the relationship between word reading and comprehension. Similarly, a study by Tran et al [91] found similar results in a test of vocabulary breadth and depth in a sample of 103 adults with low literacy skills.…”
Section: The Role Of Vocabulary As a Mediating Variable In Reading Co...supporting
confidence: 93%
“…Tasks for the measurement of reading comprehension LECTUM 7-Reading Comprehension Test [69]: This test involves the comprehension of explicit and implicit information at the textual, pragmatic, and critical levels in two argumentative texts-one expository and one narrative text-with 32 multiple-choice questions to be answered in 90 Reading Speed Task: This task automatically measures reading time in milliseconds of high-and low-familiarity short texts. Each text has 2 sentences (11 to 13 words) with the same syntactic structure.…”
mentioning
confidence: 99%